2021
DOI: 10.3390/vaccines9121507
|View full text |Cite
|
Sign up to set email alerts
|

Promising Expectations for Pneumococcal Vaccination during COVID-19

Abstract: The emergence of new viral infections has increased over the decades. The novel virus is one such pathogen liable for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, popularly known as coronavirus disease 2019 (COVID-19). Most fatalities during the past century’s influenza pandemics have cooperated with bacterial co/secondary infections. Unfortunately, many reports have claimed that bacterial co-infection is also predominant in COVID-19 patients (COVID-19 associated co/secondary infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…However, it has been argued that the proportion of COVID-19 patients with bacterial coinfections and/or super-infections may be lower compared to what we have seen in patients suffering from influenza [5557]. Nevertheless, since vaccination is beneficial per se, it has been suggested that pneumococcal vaccination can, to some extent, provide additional protection to the COVID-19 patients reducing the morbidity and mortality [58]. Animal studies have also shown that an initial SARS-CoV-2 infection can increase susceptibility and pathogenicity to bacterial coinfection [59].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been argued that the proportion of COVID-19 patients with bacterial coinfections and/or super-infections may be lower compared to what we have seen in patients suffering from influenza [5557]. Nevertheless, since vaccination is beneficial per se, it has been suggested that pneumococcal vaccination can, to some extent, provide additional protection to the COVID-19 patients reducing the morbidity and mortality [58]. Animal studies have also shown that an initial SARS-CoV-2 infection can increase susceptibility and pathogenicity to bacterial coinfection [59].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been argued that the proportion of COVID-19 patients with bacterial coinfections and/or super-infections may be lower compared to what we have seen in patients suffering from influenza [ 82 , 83 , 84 ]. Nevertheless, since vaccination is beneficial per se, it has been suggested that pneumococcal vaccination can, to some extent, provide additional protection to COVID-19 patients, reducing the morbidity and mortality [ 85 ]. Animal studies have also shown that an initial SARS-CoV-2 infection can increase susceptibility and pathogenicity to bacterial coinfection [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, S. pneumoniae was deemed to be the most common co-infecting pathogen with a 59.5% coinfection rate in COVID-19 patients. 13 …”
Section: Imaging Of Covid-19mentioning
confidence: 99%
“…In addition, it is imperative that patients at high risk for superimposed pneumococcal infection obtain their pneumococcal vaccine for prevention. 13 …”
Section: Imaging Of Covid-19mentioning
confidence: 99%